2021
DOI: 10.1371/journal.pone.0250044
|View full text |Cite
|
Sign up to set email alerts
|

Etiologies of genital inflammation and ulceration in symptomatic Rwandan men and women responding to radio promotions of free screening and treatment services

Abstract: Introduction The longstanding inadequacies of syndromic management for genital ulceration and inflammation are well-described. The Rwanda National Guidelines for sexually transmitted infection (STI) syndromic management are not yet informed by the local prevalence and correlates of STI etiologies, a component World Health Organization guidelines stress as critical to optimize locally relevant algorithms. Methods Radio announcements and pharmacists recruited symptomatic patients to seek free STI services in K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 59 publications
1
3
0
Order By: Relevance
“…The combination of genital inflammation and higher HIV viremia significantly increases the risk for HIV transmission. 52 Findings from the current study add to the growing body of research on HIV disclosure to sex partners in the era of U=U. Similar to past research, we found that disclosing one's HIV status clustered with disclosure across multiple relationships.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The combination of genital inflammation and higher HIV viremia significantly increases the risk for HIV transmission. 52 Findings from the current study add to the growing body of research on HIV disclosure to sex partners in the era of U=U. Similar to past research, we found that disclosing one's HIV status clustered with disclosure across multiple relationships.…”
Section: Discussionsupporting
confidence: 84%
“…The combination of genital inflammation and higher HIV viremia significantly increases the risk for HIV transmission. 52…”
Section: Discussionmentioning
confidence: 99%
“…As expected, C. albicans was the most common species, but 27% of women with VVC had non– albicans Candida species, especially C. glabrata , C. tropicalis , and C. krusei. 15–19 Interestingly, 24% of C. albicans and 80% of non– albicans Candida strains showed in vitro resistance to the first-line drug, fluconazole. These rates of antifungal resistance are in line with reports from other parts of the world, such as Cameroon and Uganda, as well as a previous report that included a different cohort from Namibia 20–22 .…”
Section: Discussionmentioning
confidence: 99%
“…Candida species were detected in 110 (43%) of swabs collected from women with VDS in our study making it the most common microbial aetiology. Studies from sub-Saharan Africa reported a wide range of Candida prevalence in women with VDS: 21% in Rwanda [ 29 ], 25% in Ethiopia [ 30 ], 26% in Mauritania [ 31 ], 29% in Senegal and Gabon [ 15 , 32 ], 38% in Cameroon [ 33 ], 39% in Benin [ 34 ], 45% in South Africa [ 35 ], 49% Burkina Faso [ 36 ], 55% in Nigeria [ 37 ] and 66% in Tanzania [ 38 ]. The geographic differences in the reported prevalence described in different settings might be owing to environmental, behavioural, socioeconomic factors, as well differences in study methodologies [ 30 ].…”
Section: Discussionmentioning
confidence: 99%